Growth Hormone Supplementation May Not Improve Live Birth Rate in Poor Responders - Zhu, Jinliang; Wang, Ying; Chen, Lixue; Liu, Ping; Li, Rong; Qiao, Jie (Frontiers in Endocrinology, 2020)
Backgrounds: Growth hormone (GH) was used for many years to increase ovarian response in poor ovarian responders (PORs). Although meta-analysis suggested that GH therapy improve early clinical outcomes, the benefit of GH usage on chance of live birth was still widely debated. This study was to determine whether or not GH supplementation influences the live birth rate (LBR). Methods: A total of 3080 expected PORs receiving and not receiving (control) GH adjuvant therapy at Peking University Third Hospital from January 2017 to March 2018 were retrospectively analyzed. The basal characteristics of patients were compared using analysis of variance (continuous variables) and categorical variables were evaluated with a chi-square test. Logistic regression analyses were used to evaluate potential associations of LBR with GH treatment while adjusting other confounding factors. Results: no statistically significant differences existed in miscarriage rate (5.3% vs. 12.5%; p=0.076) and LBR (37.7% vs. 34.5%; p=0.426) in young expected PORs (< 35 years of age). Moreover, no significant differences existed in the miscarriage rate (25.6% vs. 23.3%; p=0.681), and LBR (17.8% vs. 17.9%; p=0.977) in the old expected PORs (≥ 35 years of age). Logistic regression suggested that GH adjuvant therapy did not improve the LBR in young (OR, 1.27; 95% CI, 0.88 - 1.85; p=0.203) and elderly expected PORs (OR, 1.20; 95% CI, 0.82 - 1.76; p=0.342). In subgroup analysis, GH treatment significantly increased the day 3 embryos available rate in the subgroup of young PORs with the long down-regulation (63.11% vs. 49.35%; p=0.004), while significantly reduced the risk of miscarriage in the subgroup of young PORs with GnRH antagonist protocol (0.00% vs. 12.61%; p=0.023). There was no significant difference for LBR in PORs with GnRH antagonist (<35 years [35.19% vs. 28.45%; p=0.183]; ≥35 years [12.96% vs. 14.03%; p=0.707]), GnRH-a long (<35 years [33.33% vs. 36.99%; p=0.597]; ≥35 years [17.44% vs. 20.28%; p=0.574]) and long down-regulation (<35 years [58.82% vs. 41.90%; p=0.193]; ≥35 years [43.33% vs. 25.30%; p=0.065]). Conclusions: Growth hormone treatment may not improve live birth rate in expected poor responders.